A Theory of Learning Based on Constructivism and Problem-Based Learning to Develop Higher Order Thinking Skills - John, Trixy Elizabeth; Thomas, Dr.Fr.Benny (IJRDO - Journal of Social Science and Humanities Research, 2018)
The constructivist view of learning holds that meaningful learning occurs when people construct knowledge with the help of existing schemas and the viewpoints of others. Problem- based learning is one of the approaches that can be used in a constructive classroom to produce meaningful learning. In the constructivist classroom, students are not passive listeners. Students frequently engage in meaningful, problem-based activities and in such high-level cognitive processes which fosters creativity and motivation. It provides students with minds-on and hands-on experience. Problem-based learning presents students with authentic problems and requires them to discover sufficient information that they need to solve the problem through scaffolded instruction, and social interaction. This paper presents a study of the problem- based learning in a constructivist setting. The suggested elements of the theory that defines a constructivist classroom are providing guided instruction for the analysis of the problem within the zone of proximal development, providing opportunities for self-instruction using computer-supported learning tactics, providing opportunities for collaborative based inquiry approach and incorporating interdisciplinary approach to foster meaningful learning. This problem-based learning based on the constructivist theory will help students to be self-directed and for the development of thinking skills.